Comparing humoral immune response to SARS‐CoV2 vaccines in people with multiple sclerosis and healthy controls: An Austrian prospective multicenter cohort study. (9th February 2022) - Bsteh, Gabriel; Hegen, Harald; Traxler, Gerhard; Krajnc, Nik; Leutmezer, Fritz; Di Pauli, Franziska; Kornek, Barbara; Rommer, Paulus; Zulehner, Gudrun; Dürauer, Sophie; Bauer, Angelika; Kratzwald, Sarah; et al.
Abstract: Background and purpose: SARS‐CoV2 vaccination is recommended for patients with multiple sclerosis (pwMS), but response may be limited by disease‐modifying‐treatments (DMTs). The aim of this study was to compare the rates of humoral immune response and safety of SARS‐CoV‐2 vaccines in pwMS and healthy controls (HCs). Methods: In this multicenter prospective study on 456 pwMS and 116 HCs, SARS‐CoV‐2‐IgG response was measured 3 months after the first vaccine dose. The primary endpoint was defined as proportion of patients developing antibodies (seroconversion). Secondary endpoints included antibody level, safety and efficacy. Results: Compared to 97.4% in HCs, seroconversion occurred in 96.7% (88/91) untreated pwMS, 97.1% of patients (135/139) on immunomodulatory DMTs and 61.1% (138/226; p < 0.001) on immunosuppressive DMTs. Seroconversion was lowest in patients on antiCD20 monoclonal antibodies (CD20 mAbs; 52.6%) followed by sphingosine‐1‐phosphate‐receptor‐modulators (S1PMs; 63.6%). In the S1PM subgroup, seroconversion increased with lymphocyte count (odds ratio [OR] 1.31 per 0.1 G/L; p = 0.035). In pwMS on CD20 mAbs, B‐cell depletion decreased seroconversion (OR 0.52; p = 0.038), whereas time since last DMT did not. Safety of SARS‐CoV‐2 vaccines in pwMS was excellent. Conclusions: Humoral response to SARS‐CoV2 vaccines in pwMS is generally excellent. While reduced by immunosuppressive DMTs, most importantly by B‐cell‐depleting CD20 mAbs and S1PMs, seroconversion is still expected in the majority of patients. SARS‐CoV2 vaccination should be offered to every MS patient. Abstract : Seroconversion and antibody levels after SARS‐CoV2 vaccination were comparable to healthy controls, in untreated patients with MS or MS patients on immunomodulatory DMTs, but significantly reduced (61.1%) on immunosuppressive DMTs (p<0.001).